An Investigation of the Effectiveness of Arts Therapies Interventions on Measures of Quality of Life and Wellbeing: A Pilot Randomized Controlled Study in Primary Schools - Moula, Zoe; Powell, Joanne; Karkou, Vicky (Frontiers in Psychology, 2020)
Background: Over the last decades there has been a change in the way schooling is perceived recognizing that children’s learning is closely linked to children’s health. Children spend most of their time at school, which is often the place where problems are identified and interventions are offered, not only for treatment but also prevention. Embedding arts therapies into the educational system may help address children’s emerging needs and have a positive impact on their wellbeing. Methods: A pilot cross-over randomised controlled design was employed to investigate the effectiveness of an arts therapies intervention on a series of child- and teacher-reported outcome measures, specifically, health-related quality of life (assessed using a HRQOL scale; EQ-5D-Y), wellbeing and life functioning (assessed using the child outcome rating scale; CORS), emotional and behavioural difficulties (assessed using the strengths and difficulties questionnaire; SDQ), and duration of sleep (assessed using Fitbits). Sample size calculations for future large-scale studies were also performed, and the sustained impact of the intervention was evaluated at 3, 6, and 12 months follow-up. The pluralistic theoretical and therapeutic framework of this intervention was informed by a systematic review on school-based arts therapies interventions (Moula et al., 2020) and was presented in detail in the study protocol (Moula et al., 2019). Participants were 62 children with mild emotional and behavioural difficulties. Results: Improvements in HRQOL and CORS were greater in those engaged in the arts therapies intervention than the control groups and were maintained at the follow-up stages. Significant improvements were only found for duration of sleep (P=0.002) and SDQ (P=0.008). Minimal clinically important differences (MCIDs) as defined in the protocol (Moula et al., 2019) were found for CORS, SDQ and duration of sleep, but not HRQOL. Discussion: Findings indicate that the arts therapies interventions were having a clinically significant effect on life functioning, duration of sleep, emotional and behavioural difficulties. Findings also indicate a small positive effect size for health-related quality of life. The study indicates that all outcome measures would be suitable for inclusion in a larger randomised controlled study, and that a sample size of 225 participants would be required.